Investigation of rheological properties of semi-finished products for oriental confectionery based on gluten-free raw materials - M. V. Cherkunova; A. R. Abushaeva; M. K. Sadygova; N. A. Semilet (Современная наука и инновации)
This article is devoted to the study of rheological properties of finished dough semi-finished products for oriental confectionery based on gluten-free raw materials. Rice and corn flour were used as the main raw materials. Foam density was determined as the ratio of a certain foam mass to the volume of the vessel measured with distilled water, foaming ability – as the ratio of the height of the foam column to the height of the column of the solution of prescription components, foam stability – as the ratio of the height of the foam after 3 hours to the original. Organoleptic quality indicators were determined in accordance with GOST R 50228-92. The tasting quality assessment was carried out by a 10-point school. The structural and mechanical properties of the chak-chak samples were studied on the texture analyzer "Structurometer ST-3" by determining the loading force on the indenter when it is inserted into the sample body at a movement speed (insertion) of 1.0 mm/s. As a result of the conducted research, it was concluded that the optimal ratio of rice and corn flour is 1:1, in this ratio, semi-finished products are characterized by high organoleptic and structural-mechanical quality indicators that are not inferior to the control sample of semi-finished products. The use of rice and corn flour in the chakchak technology makes it possible to expand the range of gluten-free oriental flour confectionery products suitable for consumption by people suffering from such a disease as celiac disease.